Assistant to the villain - Maehrer, Hannah Nicole (Red Tower Books, an imprint of Entangled Publishing, LLC., 2023)
"ASSISTANT WANTED: Notorious, high-ranking villain seeks loyal, levelheaded assistant for unspecified office duties, supporting staff for random mayhem and terror, and other Dark Things In General. Discretion a must. Excellent benefits. With ailing family to support, Evie Sage's employment status isn't just important, it's vital. So when a mishap with Rennedawn's most infamous Villain results in a job offer--naturally, she says yes. No job is perfect, of course, but even less so when you develop a teeny crush on your terrifying, temperamental, and undeniably hot boss. Don't find evil so attractive, Evie. But just when she's getting used to severed heads suspended from the ceiling and the odd squish of an errant eyeball beneath her heel, Evie suspects this dungeon has a huge rat...and not just the literal kind. Because something rotten is growing in the kingdom of Rennedawn, and someone wants to take the Villain--and his entire nefarious empire--out. Now Evie must not only resist drooling over her boss but also figure out exactly who is sabotaging his work...and ensure he makes them pay. After all, a good job is hard to find"--